A Rare Case Report: Leigh Syndrome - C Wali, Shashikala; Shah, Mithilesh; Sheikh, Chandani; Parihar, Ashish Singh; Ganachari, MS (Indian Journal of Pharmacy Practice)
It is a case report on a very rare type of Leigh Syndrome (LS) that is adult-onset subacute necrotizing encephalopathy which generally begun during adolescence or early adulthood. It is characterized by degeneration of the CNS, severe failure of oxidative metabolism, vision impairment, impairment of respiratory, heart and kidney function. According to some resources incidence of occurring LS is 1 in 40,000 new born and unusually in adult hood. Characteristics lesion in basal ganglia associated with demyelination. Primary feature includes: subacute relapsing encephalopathy with cerebral and brain-stem signs presenting during infancy. Additional feature includes: basal ganglia lucencies. The prognosis for LS is very poor. Patients lacking mitochondrial complex IV activity and deficiency in pyruvate dehydrogenase have worst prognosis and die within a few years. Patients with partial deficiencies have better prognosis and can live up to 6 to 7 years of age. Some have survived to their mid-teenage years.
Keywords: Sub-acute necrotizing encephalopathy; Oxidative metabolism; Basal ganglia; Lucencies; Mitochondrial complex; Pyruvate dehydrogenase.